Dysphagia is not a Valuable Indicator of Tumor Response after Preoperative Chemotherapy for R0 Resected Patients with Adenocarcinoma of the Gastroesophageal Junction. (June 2016) - Strandby, R. B.; Svendsen, L. B.; Bæksgaard, L.; Egeland, C.; Achiam, M. P.
Background: Monitoring treatment response to preoperative chemotherapy is of utmost importance to avoid treatment toxicity, especially in non-responding patients. Currently, no reliable methods exist for tumor response assessment after preoperative chemotherapy. Therefore, the aim of this study was to evaluate dysphagia as a predictor of tumor response after preoperative chemotherapy and as a predictor of recurrence and survival. Methods: Patients with adenocarcinoma of the gastroesophageal junction, treated between 2010 and 2012, were retrospectively reviewed. Dysphagia scores (Mellow-Pinkas) were obtained before and after three cycles of perioperative chemotherapy together with clinicopathological patient characteristics. A clinical response was defined as improvement of dysphagia by at least 1 score from the baseline. The tumor response was defined as down staging of T-stage from initial computer tomography (CT) scan (cT-stage) to pathologic staging of surgical specimen (pT-stage). Patients were followed until death or censored on June 27th, 2014. Results: Of the 110 included patients, 59.1% had improvement of dysphagia after three cycles of perioperative chemotherapy, and 31.8% had a chemotherapy-induced tumor response after radical resection of tumor. Improvement of dysphagia was not correlated with the tumor response in the multivariate analysis (p = 0.23). Moreover, the presence of dysphagia was not correlated with recurrence (p = 0.92) or survival (p = 0.94) in the multivariate analysis. Conclusion: In our study, improvement of dysphagia was not valid for tumor response evaluation after preoperative chemotherapy and was not correlated with the tumor response. The presence of dysphagia does not seem to be a predictor of recurrence or survival.